subtract (-9x^2+8x-14) from the sum of (-9x^2-10x) and (3x^2+3x+7)​

Question

subtract (-9x^2+8x-14) from the sum of (-9x^2-10x) and (3x^2+3x+7)​

in progress 0
Maya 2 weeks 2021-11-23T12:18:34+00:00 1 Answer 0

Answers ( )

    0
    2021-11-23T12:19:54+00:00

    Answer:

    3x^2 - 15x + 21\\or\,\,3(x^2 -5x +7)

    Step-by-step explanation:

    First we will find sum of (-9x^2-10x)\,\, and\,\, (3x^2+3x+7)

    Adding the like terms:

    = -9x^2-10x + 3x^2 +3x+7\\= -9x^2+ 3x^2 -10x+3x+7\\= -6x^2 - 7x +7

    Now subtract (-9x^2+8x-14) from (-6x^2 – 7x +7)

    =(-6x^2 - 7x +7) - (-9x^2+8x-14)\\= -6x^2 - 7x +7 +9x^2-8x+14\\= -6x^2 +9x^2 - 7x -8x+7 +14\\= 3x^2 - 15x + 21\\=3(x^2 -5x +7)

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )